IMPACT OF GENDER-BASED VIOLENCE ON THE HEALTH OF WOMEN - Pinto, Nélida (2015)
Gender-based violence expresses the power imbalance between men and women, transgresses women’s human rights and is a public health problem. Its existence is ancient and compromises societies around the world. Over one third of women has suffered violence , either psychological, physical, or sexual . Sexual violence is the most extreme version of violence against women usually concurrent with the other two types of violence. Pregnancy is not a protective factor. Victims’ closest persons, such as her current or late couple, family or known persons usually with authority on her, are the most common perpetrators. Some associated factors can be identified like alcoholism, ignorance, social permissibility, couple faulty relation, drug use and others. Consequences may be in the short, and in the mediate and long term, and deal with physical health, mental health and social impact. On physical health include suicide, homicide and both AIDS-derived and  pregnancy complications deaths; light and serious lesions, pelvic and sexual transmitted infections, ectopic pregnancies, unplanned pregnancies, spontaneous or induced abortions, low birth weight and other pregnancy complications. Psychological repercussions include depression, anxiety, post traumatic syndrome, post violation syndrome, sleep disturbances, obesity, alcohol and drug consumption, tobacco consumption and sexual risky conducts, among others. Social impact may be verified by health care- and legal care-derived costs as well as implications on productivity and employment. Due to the serious repercussions of violence on women and society in general, it should be confronted with information, education, work with men groups and better health services readiness, legal and social support.